Pengembangan Media Pembelajaran menggunakan Construct 2 pada Materi Relasi dan Fungsi untuk Kelas VIII SMP - Beby Meidhita Syam; Nur Izzati (JURNAL EKSAKTA PENDIDIKAN (JEP), 2020)
This study aims to develop a learning media by using construct 2 to the material of relations and functions. The type of research is research and development with the 4D model were define, design, development, and disseminate. The subjects of this study were students of class VIII F Junior High School 3 Bintan amounting to 32 people in the 2019/2020 academic year. The research data was collected by using a validation technique involving 2 expert validators, each material expert and media expert, also collected by a questionnaire responding from educators and students. The research instrument consisted of validation sheets and questionnaire sheets. The research data were analyzed by changing ordinal data into interval data with the rating scale technique. The percentage of acquisition is calculated to get the category of validity and practicality. The results of this study based on the validation of material experts obtained 88.23% are in very valid criteria and validation of media experts obtained 83.33% are in very valid criteria. The response by students obtained 88.84% are in very practical criteria and from educators obtained 91.67% are in very practical criteria.